2000
DOI: 10.1161/01.atv.20.11.2434
|View full text |Cite
|
Sign up to set email alerts
|

Normal Oxidative Stress and Enhanced Lipoprotein Resistance to In Vitro Oxidation in Hypertriglyceridemia

Abstract: Abstract-Although there is evidence that hyperlipidemia and predominance of small dense low density lipoproteins (LDLs) are associated with increased oxidative stress, the oxidation status in patients with hypertriglyceridemia (HTG) has not been studied in detail. Therefore, we studied urinary levels of F 2 -isoprostanes (8-isoprostaglandin F 2␣ and 2,3-dinor-5,6-dihydro-8-isoprostaglandin F 2␣ ) and susceptibility of very low density lipoproteins (VLDLs) and LDLs to oxidation ex vivo in 18 patients with endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…A total of 83 trials (53 trials for fibrates and 30 trials for niacin) met our criteria and were included in the meta-analysis (Tables 1 and 2). The distribution of the 53 trials with fibrates is as follows: 17 trials with gemfibrozil (5,6,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), 15 trials with fenofibrate (22,28 -41), 13 trials with bezafibrate (22,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53), 9 trials with clofibrate (21,54 -61), and 2 trials with ciprofibrate (62,63). For the 30 trials with niacin, the distribution is as follows: 11 trials with immediate-release niacin (IR-niacin) (54,64 -73), 10 trials with acipimox (72,74 -82), 6 trials with extended-release niacin (ER-niacin) (67,(83)(84)(85)(86)(87), and 5 trials with wax-matrix sustained-release niacin (SR-niacin) (64,88 -91).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 83 trials (53 trials for fibrates and 30 trials for niacin) met our criteria and were included in the meta-analysis (Tables 1 and 2). The distribution of the 53 trials with fibrates is as follows: 17 trials with gemfibrozil (5,6,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), 15 trials with fenofibrate (22,28 -41), 13 trials with bezafibrate (22,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53), 9 trials with clofibrate (21,54 -61), and 2 trials with ciprofibrate (62,63). For the 30 trials with niacin, the distribution is as follows: 11 trials with immediate-release niacin (IR-niacin) (54,64 -73), 10 trials with acipimox (72,74 -82), 6 trials with extended-release niacin (ER-niacin) (67,(83)(84)(85)(86)(87), and 5 trials with wax-matrix sustained-release niacin (SR-niacin) (64,88 -91).…”
Section: Resultsmentioning
confidence: 99%
“…The body mass index of patients in trials with fibrates and niacin was 27 and 28 kg/m 2 , respectively. Twelve trials used random assignment with a crossover design (19,21,26,27,38,40,42,45,51,57,58,61). Subjects with the following dyslipidemias and study populations were enrolled into the 83 trials: 29 trials with hypercholesterolemia (5,(22)(23)(24)(25)28,33,34,36,43,49,52,53,(55)(56)(57)59,60,62,64,67,(85)(86)(87)(88)(89)(90)92); 25 trials with type II diabetes mellitus (15,17,18,20,29,31,32,37-39,41,43,44,46,50,57,65,68,76 -79,81-83); 16 trials with combined hyperlipidemia (21,27,28,33,38,44,…”
Section: Resultsmentioning
confidence: 99%
“…Thus, de Man et al showed in a study in patients with endogenous hypertriglyceridemia that bezafibrate therapy (400 mg/d) was associated with normalisation of oxidation resistance of isolated lipoproteins and an increase in urinary excretion of 8-iso-PGF 2␣ [65], presumably as a result of elevated hepatic lipid oxidation [66]. As urinary excretion of 8-iso-PGF 2␣ may be elevated during high-rate lipid metabolism [65], it is likely that elevation of urinary 8-iso-PGF 2␣ excretion is a result of enhanced lipid metabolism accompanying lipid-lowering therapy with statins and fibrates ( [65] and present study), rather than elevation of lipid peroxidation.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Exposure of TG-enriched LDL to hepatic lipase (HL), the activity of which is increased in patients with HTG, [29,30] increases hydrolysis of LDL, leading to the formation of small dense LDL. [35] In conclusion, the abundance of TGs saturates the normal routes of lipoprotein removal, resulting in impaired reverse cholesterol transport and the formation of a highly atherogenic lipid profile, including high serum TG levels, low HDL-C levels and elevated small dense LDL levels. [31] To test whether HTG is associated with increased oxidative stress, de Man et al [35] measured urinary levels of F 2 -isoprostanes, chemically stable endproducts of lipid peroxidation, in patients with HTG.…”
Section: Lipid and Lipoprotein Profilementioning
confidence: 98%
“…[27,28] In addition, because of the long residence time of LDL in plasma, LDL interacts with VLDL through CETP as well, resulting in TG-enriched LDL and cholesteryl ester-enriched VLDL. [31] To test whether HTG is associated with increased oxidative stress, de Man et al [35] measured urinary levels of F 2 -isoprostanes, chemically stable endproducts of lipid peroxidation, in patients with HTG. [31] Small dense LDL has been associated with increased cardiovascular risk, [32] probably through its increased affinity for arterial proteoglycans, [33] its efficient infiltration into the arterial wall, [34] and its increased susceptibility to oxidative modification.…”
Section: Lipid and Lipoprotein Profilementioning
confidence: 99%